Vibration Analysis of Cylindrical Sandwich Aluminum Shell with Viscoelastic Damping Treatment - Tai-Hong Cheng; Zhen-Zhe Li; Yun-De Shen (Advances in Materials Science and Engineering)
This paper has applied the constrained viscoelastic layer damping treatments to a cylindrical aluminum shell using layerwise displacement theory. The transverse shear, the normal strains, and the curved geometry are exactly taken into account in the present layerwise shell model, which can depict the zig-zag in-plane and out-of-plane displacements. The damped natural frequencies, modal loss factors, and frequency response functions of cylindrical viscoelastic aluminum shells are compared with those of the base thick aluminum panel without a viscoelastic layer. The thickness and damping ratio of the viscoelastic damping layer, the curvature of proposed cylindrical aluminum structure, and placement of damping layer of the aluminum panel were investigated using frequency response function. The presented results show that the sandwiched viscoelastic damping layer can effectively suppress vibration of cylindrical aluminum structure.